Developing the Corporate Global Leadership Bench Strength through Transformational Leaders - Wijewantha , Prabhashini (Asian Journal of Empirical Research, 2019)
Developing the global leadership bench strength by advancing the global leadership competencies of high potential employees is a critical concern for Multinational Corporations (MNCs), to achieve sustainable competitive advantage. Accordingly, the main purpose of this paper is to emphasize the role of line managers transformational leadership in developing the global leadership competencies of their respective subordinates, with the theoretical support of the transformational leadership theory. For the above purpose, data were collected from line manager-high potential dyads, using a structured questionnaire developed using well accepted, standard measures. Upon completion of preliminary analyses, the hypothesis was tested. From the regression analyses, it was found that there is a major impact of line manager's transformational leadership in the development of global leadership competencies of high potential subordinates. This finding is consistent with the transformational leadership theory and other empirical studies in the area and suggests the development of line manager's transformational leadership competencies for the purpose of developing the global leadership bench strength in MNCs.